The Influence of the Project Based Learning Model Assisted by PhET Simulations on Students' Generic Science Skills in Energy Source Materials - Dewi Lestari; Aris Doyan; Muhammad Taufik; Satutik Rahayu (Postgraduate, University of Mataram, 2024)
This research aims to determine the effect of the Project Based Learning model assisted by PhET simulations on students' generic science skills in energy sources. The type of research used in this research is quasi-experimental with a pre-test post-test control group design. The population in this study was all class The research sample was taken using purposive sampling, so that 28 class X1 students were selected as the experimental class and 22 class X2 students as the control class. The independent variable in this research is the Project Based Learning model assisted by PhET simulations which is used in the experimental class, while generic science skills are the dependent variable. The instrument used to measure generic science skills is a test instrument in the form of a multiple choices test with 10 questions. The results of pre-test data analysis showed that students' initial knowledge was almost the same, but after being given treatment the average post-test score for the experimental class was 80.00 and the control class was 71.67. The results of the t test using the Independent Sample T-test in the post-test showed a significance (2 tailed) of 0.018 < 0.050, so it can be concluded that the Project Based Learning model assisted by PhET simulations has an effect on students' generic science skills in energy sources.